Rancang Bangun Sistem Pengunci Pintu Berbasis RFID dan Arduino pada Laboratorium Komputer Jurusan Teknik Informatika - Fendi Hermawanto; Hilda Jaya Habibi; Nur Cholik Hasyim (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
The development of technology is currently growing rapidly, especially door lock technology. The door at the informatics engineering laboratory still uses a manual lock system using a key. There are weaknesses in this system, starting from security, namely currently many people can duplicate keys. While in terms of key care, if the key is lost, you must first go to the key duplication area. Therefore, the research team needs to design a door lock system based on Rfid and Arduino in the Computer Laboratory of the Department of Informatics. The purpose of this research is to keep up with the times, which are all automated, to facilitate the process of opening and closing the laboratory door, and to facilitate maintenance. The materials needed to make this system include Pro Micro, RFID sensor, Selenoid door lock, LED, 5V relay module, ID card and acrylic. This research was conducted at the Laboratory of the Informatics Engineering Department of the Banyuwangi State Polytechnic. The method used is the Research and Development (R&D) method, the R&D method is a method for making a product and testing its effectiveness. The stages of the R&D method are potential and problems, system design, tool manufacture and refinement, tool testing. The results of this study are that the research objectives have been fulfilled in facilitating the process of opening and closing laboratory doors and can overcome security problems and key duplication.